Human Brucellosis Trends: Re‐emergence and Prospects for Control Using a One Health Approach in Azerbaijan (1983–2009). (25th September 2015) - Kracalik, I. T.; Abdullayev, R.; Asadov, K.; Ismayilova, R.; Baghirova, M.; Ustun, N.; Shikhiyev, M.; Talibzade, A.; Blackburn, J. K.
Summary: Brucellosis is one of the most common and widely spread zoonotic diseases in the world. Control of the disease in humans is dependent upon limiting the infection in animals through surveillance and vaccination. Given the dramatic economic and political changes that have taken place in the former Soviet Union, which have limited control, evaluating the status of human brucellosis in former Soviet states is crucial. We assessed annual spatial and temporal trends in the epidemiology of human brucellosis in Azerbaijan, 1983–2009, in conjunction with data from a livestock surveillance and control programme (2002–2009). To analyse trends, we used a combination of segmented regression and spatial analysis. From 1983 to 2009, a total of 11 233 cases of human brucellosis were reported. Up to the mid‐1990s, the incidence of human brucellosis showed a pattern of re‐emergence, increasing by 25% annually, on average. Following Soviet governance, the incidence rates peaked, increasing by 1.8% annually, on average, and subsequently decreasing by 5% annually, on average, during the period 2002–2009. Despite recent national declines in human incidence, we identified geographic changes in the case distribution characterized by a geographic expansion and an increasing incidence among districts clustered in the south‐east, compared to a decrease of elsewhere in the country. Males were consistently, disproportionately afflicted (71%) and incidence was highest in the 15 to 19 age group (18.1 cases/100 000). During the period 2002–2009, >10 million small ruminants were vaccinated with Rev1. Our findings highlight the improving prospects for human brucellosis control following livestock vaccination; however, the disease appears to be re‐emerging in south‐eastern Azerbaijan. Sustained one health measures are needed to address changing patterns of brucellosis in Azerbaijan and elsewhere in the former Soviet Union.